"n Hermeneutiek vir Teologiese interpretasie van die Bybel: Metodologiese besinning - Viljoen, Anneke (2017)
The publication of several series of theological commentaries since the year 2000 marked theentrance of the discipline Theological interpretation of the Bible on the hermeneutical front. Alack of well-developed methodological considerations, underlying the practice of Theologicalinterpretation of the Bible has, however, handicapped the theological interpretation of Bibletexts. It is the aim of this article to contribute to the development thereof. Three meta-hermeneutical aspects that make up the broad methodological foundation of Theologicalinterpretation of the Bible, namely metaphysics, epistemology and ethics are explored.
Keywords: Hermeneutiek; Metodologiese Oorwegings; Teologiese Interpretasie